Sister Species : Women, Animals and Social Justice - Kemmerer, Lisa (Book collections on Project MUSE., 2011)
"There is a very strong association between women, animals, and activism. In Women, Social Justice, and Animal Advocacy, activist Lisa A. Kemmerer presents the narratives of fourteen ecofeminist activists who describe their own experiences in the field, often from the perspective of discovering the extent of a particular kind of animal oppression and resolving to do something about it. The narratives are bold and gripping, sometimes horrifying, and cover a range of topics relating to animal rights and liberation. The writers discuss contemporary cockfighting, factory farming, orphaned primates in Africa, the wild bird trade, scientific experimentation on animals, laws against "dangerous" dogs, and violence against baby seals. Sister Species provides a wide survey of what women are doing in the animal activism movement. The writers ask readers to rethink how we view animals in our daily lives--and how we can take action to protect them. Kemmerer's introduction explains why she collected these particular stories and how she views the relationship between feminism and animal suffering. The foreword is by Carol J. Adams, author of The Sexual Politics of Meat (1990), Neither Man nor Beast: Feminism and the Defense of Animals.(1994), The Feminist Care Tradition in Animal Ethics: A Reader (2007), and many other books. None of these essays has been previously published"--